2006
DOI: 10.1103/physrevb.74.045201
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy switching in(Ga,Mn)Aswith increasing hole concentration

Abstract: We study a possible mechanism of the switching of the magnetic easy axis as a function of hole concentration in (Ga,Mn)As epilayers. In-plane uniaxial magnetic anisotropy along [110] is found to exceed intrinsic cubic magnetocrystalline anisotropy above a hole concentration of p = 1.5 × 10 21 cm −3 at 4 K. This anisotropy switching can be realized by post-growth annealing, and the temperature-dependent ac susceptibility is significantly changed with increasing annealing time. On the basis of our recent scenar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] In spite of different experimental conditions, the in-plane uniaxial anisotropy was observed for (Ga,Mn)As films in a thickness range from 25 nm (Ref. 20) to 500 nm, 16 irrelevant with respect to the surface condition.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[11][12][13][14][15][16][17][18] In spite of different experimental conditions, the in-plane uniaxial anisotropy was observed for (Ga,Mn)As films in a thickness range from 25 nm (Ref. 20) to 500 nm, 16 irrelevant with respect to the surface condition.…”
mentioning
confidence: 99%
“…2,3,7 The strength of the MCA depends on the hole concentration introduced by the Mn impurity atoms 2,11,18,19 as well as on the variation of the equilibrium lattice parameter of (Ga,Mn)As, which increases with increasing Mn content and results thus in a larger lattice mismatch with the GaAs substrate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…͑Ga,Mn͒As exhibits hole-mediated ferromagnetism 1,2 and its magnetic anisotropy depends on hole concentration, Mn concentration, lattice strain, and spin-orbit interaction. [2][3][4][5][6][7] Recently, magnetization vector rotation by an electric field has been demonstrated in ͑Ga,Mn͒As, 8 and both experiments and simulations have shown that the modulation of the uniaxial anisotropy along ͗110͘ plays an important role in magnetization switching. 9 One of the methods for controlling the uniaxial anisotropy is the modulation of the lattice strain in ͑Ga,Mn͒As.…”
mentioning
confidence: 99%